Joyful Experiences in Physical Education and Students’ Readiness to Exercise: Evidence of an Unexpected Negative Association - Putra, Anandito Hadi Eko; S, Adi (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
This study examined the relationship between joyful experiences in physical education and students’ readiness to exercise. A quantitative correlational design was employed involving 274 secondary school students in Semarang, Indonesia. Joyful experiences were measured using the Physical Activity Enjoyment Scale (PACES), while readiness to exercise was assessed through a structured questionnaire including intention, intrinsic motivation, self-confidence, and behavioral readiness. Data were analyzed using non-parametric correlation due to non-normal distribution. Prior to analysis, data verification procedures were conducted, including reverse coding of negatively worded items, consistency checks of scoring direction, and outlier screening using standardized Z-scores, ensuring that the results were not influenced by coding errors. The findings indicated that both joyful experiences (M = 3.54, SD = 0.39) and readiness to exercise (M = 3.95, SD = 0.60) were relatively high. However, Spearman’s correlation revealed a significant negative relationship (ρ = -0.415, p < 0.001), which was confirmed by Kendall’s tau-b (τ = -0.299, p < 0.001). This unexpected result suggests that joyful experiences in physical education may remain situational and do not automatically translate into readiness for independent physical activity. The findings highlight the importance of autonomy-supportive learning environments in transforming positive affect into sustainable behavioral readiness.